A Review On Wireless Sensor Networks Routing Protocol:Challenge In Energy Perspective - Ismail Ahmedy; Md. Asri Ngadi; Syaril Nizam Omar; Junaid Chaudhry (Academic Journals, 2024)
Wireless sensor networks (WSNs) technology consists of a number of sensor nodes that are dispersed in a geographically distributed area usually for monitoring purposes. The widespread applications of WSN have fueled the emergence and acceptance of this technology as a frontrunner. However, the success of the wireless sensor network applications highly depends on the reliable communication among the sensor nodes. One of the major problems in wireless sensor network environments is the limitation of the physical resource that is energy resources. The node energy is a critical constraint that needs addressing in order to achieve the demanding goals of wireless sensor network applications. High energy consumption in the sensor node occurs when data is disseminated to the other nodes in wireless sensor networks. Data delivery in specific time slot holds the key position for the successful completion of tasks assigned to sensor nodes and hence the application those sensors are serving. The wireless sensor network applications are in high demand nowadays. Time delay in packet delivery can save lives. The data in WSN hops from one node to another in order to reach the destination if the receiver node is not in a direct radio range of the sender. This paper provides a critical analysis on the impact of the previous methods on the reliability and energy efficiency for routing protocol in multi-hop wireless sensor networks. At the end of this paper, a characterized comparison has been forwarded on these methods based on the analysis outcome.